MODEL TEORETIKAL DASAR PENGEMBANGAN KUALITAS STRATEGI - Widodo, Widodo (JURNAL BISNIS STRATEGI, 2008)
Strategy quality is strategy was built with strategy planning, implementation and strategy evaluation which have a good quality. But the study result shows there is controversial result (research gap). It Was showed in variables of strategy planning, strategy implementation and strategy evaluation.Because of that condition, so this article have purpose to develop model of grand theory. With the developing ofstrategy which have a good quality, it was hoped can growing the increasing of organization works. So thre research agenda in the future strategy quality is the area of empirics study which is interesting to do.